Daily practice of mechanical ventilation in Italian pediatric intensive care units: a prospective survey. - Wolfler, Andrea; Calderoni, Edoardo; Ottonello, Giancarlo; Conti, Giorgio; Baroncini, Simonetta; Santuz, Pierantonio; Vitale, Pasquale; Salvo, Ida (Pediatr Crit Care Med, 2011)
OBJECTIVES: To assess how children requiring endotracheal intubation are mechanically ventilated in Italian pediatric intensive care units (PICUs). DESIGN: A prospective, national, observational, multicenter, 6-month study. SETTING: Eighteen medical-surgical PICUs. PATIENTS: A total of 1943 consecutive children, aged 0-16 yrs, admitted between November 1, 2006 and April 30, 2007. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Data on cause of respiratory failure, length of mechanical ventilation (MV), mode of ventilation, use of specific interventions were recorded for all children requiring endotracheal intubation for >24 hrs. Children were stratified for age, type of patient, and cause of respiratory failure. A total of 956 (49.2%) patients required MV via an endotracheal tube; 673 (34.6%) were ventilated for >24 hrs. The median length of MV was 4.5 days for all patients. If postoperative patients were excluded, the median time was 5 days. Bronchiolitis (6.7%), pneumonia (6.7%), and upper airway obstruction (5.3%) were the most frequent causes of acute respiratory failure, and altered mental status (9.2%) was the most frequent reason for MV. The overall mortality was 6.7% with highest rates for heart disease (nonoperative), sepsis, and acute respiratory distress syndrome (26.1%, 22.2%, and 16.7% respectively). Length of stay, associated chronic disease, severity score on admission, and PICU mortality were significantly higher in children who received MV (p < .05) than in children who did not. Controlled MV and pressure support ventilation + synchronized intermittent mandatory ventilation were the most frequently used modes of ventilatory assistance during PICU stay. CONCLUSIONS: Mechanical ventilation is frequently used in Italian PICUs with almost one child of two requiring endotracheal intubation. Children treated with MV represent a more severe category of patients than children who are breathing spontaneously. Describing the standard care and how MV is performed in children can be useful for future clinical studies.
Keywords: Adolescent; Child; Child, Preschool; Clinical Protocols; Female; Humans; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Intubation, Intratracheal; Italy; Male; Prospective Studies; Respiration, Artificial; Respiratory Insufficiency